2023
DOI: 10.3390/vaccines11040772
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Knowledge of Pneumococcal Vaccination in Cardiology Outpatient Clinics and the Impact of Physicians’ Recommendations on Vaccination Rates

Abstract: Aim: We aimed to evaluate the awareness of pneumococcal vaccination (PCV13, PPSV23) in general cardiology outpatient clinics and impact of physicians’ recommendations on vaccination rates. Methods: This was a multicenter, observational, prospective cohort study. Patients over the age of 18 from 40 hospitals in different regions of Turkey who applied to the cardiology outpatient clinic between September 2022 and August 2021 participated. The vaccination rates were calculated within three months of follow-up fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In a study conducted in Turkey regarding pneumococcal vaccines (PCV13 and PPSV23), vaccine safety and benefit were a concern to the general population. Vaccine safety is a serious issue that makes patients reluctant to use these vaccines 37 .…”
Section: Vaccine Safety and Considerations In Hf Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted in Turkey regarding pneumococcal vaccines (PCV13 and PPSV23), vaccine safety and benefit were a concern to the general population. Vaccine safety is a serious issue that makes patients reluctant to use these vaccines 37 .…”
Section: Vaccine Safety and Considerations In Hf Patientsmentioning
confidence: 99%
“…Many factors affect the vaccine acceptance rate in patients like preexisting comorbidities, socioeconomic status, access to healthcare, and psychological factors (knowledge about the vaccine, attitude towards healthcare services, and perception of vaccine side effects) 37 . In one of the studies done on the barriers related to influenza vaccine uptake, it was concluded that limited vaccine knowledge and negative attitude toward healthcare services were the main factors affecting its acceptance rate 60 .…”
Section: Barriers and Challenges To Vaccination In Hf Patientsmentioning
confidence: 99%